Pengaruh Faktor Sosial, Ekonomi, Dan Demografi Terhadap Penggunaan Kontrasepsi Di Denpasar - Dyastari Saskara, Ida Ayu Gde; Marhaeni, Anak Agung Istri Ngurah (Jurnal Ekonomi Kuantitatif Terapan, 2015)
Control of high population growth rate can be done by setting restrictions on the number of children by contraceptive methods. Percentage of KB acceptors towards couples in West Denpasar is the highest around Denpasar City, yet had high number in couples that had not yet become accpetors. This study aims to determine the effect of age at first marriage, level of education of women in reproductive age, employment status, household income, and number of children on the duration of contraceptive use in West Denpasar. The number of samples is 100 respondents through interview. Analysis thecnique used is multiple linear regressions. The result showed that simultaneous variable age at first marriage, education, employment status, household income, and number of children still living longer affect the use of contraception. Partially, only the age at first marriage variable negatively affecting the duration of contraceptive use. The number of children variable is the dominant variable affecting the duration of contraceptive use in West Denpasar.
Keywords: demographic socioeconomic factors; women in reproductive age; ontraceptive use